Immediate disclosure or secrecy? The release of information in experimental asset markets - Lucy F. Ackert; Bryan K. Church; Ann B. Gillette (Federal Reserve Bank of Atlanta, 2001)
The Federal Reserve has made significant changes in its predisposition to release information over time. This paper reports the results of experimental asset markets designed to investigate how the public disclosure of uncertain information affects market and individual outcomes. In one set of markets, no information is released at the beginning of each trading year. In two other sets, an imperfect pre-announcement of the state of nature is disclosed. The reliability of the pre-announcement (60 percent and 90 percent) varies across treatments. Halfway through each trading year, the state of nature is revealed. By year-end, price deviations from Bayesian predictions are similar across all treatments; however, price volatility is significantly higher and allocational efficiency significantly lower with a pre-announcement that reflects substantial uncertainty. Furthermore, when the reliability of the pre-announcement is low (60 percent), the distribution in profit across traders is significantly greater even though the average profit is similar across treatments. Thus, in a highly uncertain environment better outcomes may actually result when information is withheld.
Keywords: 330; Monetary policy; Monetary policy - United States; Financial markets